Experimental validation and intelligent control of a stand-alone solar energy conversion system using dSPACE platform - Yahiaoui, Fatah; Chabour, Ferhat; Guenounou, Ouahib; Zaouche, Faika; Belkhier, Youcef; Bajaj, Mohit; Shouran, Mokhtar; Elgamli, Elmazeg; Kamel, Salah (Frontiers in Energy Research, 2022)
This paper presents the performances of an artificial intelligent fuzzy logic controller (FLC) based maximum power point tracking (MPPT) and a conventional perturb and observe (P&O) based MPPT controller is presented for a stand-alone PV system and tested in an emulated test bench experimentation. The studied system is composed of a DC power supply emulating the PV panel, a DC/DC boost converter, a variable resistive load and a real-time MPPT controller implemented in the dSPACE DS1104 controller. To verify the performance of the FLC proposed, several simulations have been performed in Matlab/Simulink environment. The proposed method outperforms the P&O method in terms of global search capability and dynamic performance, according to the comparison with the P&O method. To verify the practical implementation of the proposed method, the control of the emulated PV source and the MPPT algorithms are designed using the simulink/Matlab environment and implemented on dSPACE DS1104 controller. Experimental results confirm the efficiency of the proposed method and its high accuracy to handle the resistance varying.